The Role of Religious Research in Shaping an Outstanding Generation of Islamic Education at Universitas Negeri Surabaya - Fiena Saadatul Ummah; Suwantoro; Ahmad Safi’ie Hadi; Fatma; Syaifudin Noer (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The study aimed to analyze the effectiveness of religious research as a catalyst in shaping an outstanding generation of Islamic Education (PAI) students at Universitas Negeri Surabaya (UNESA) enabling them to not only master religious theories but also apply them in relevant social contexts. This approach is expected to enhance students’ critical thinking, deepen their understanding of the material, and encourage active participation in research-based PAI learning. The study discusses the implications of applying religious research to students in UNESA. How can the effectiveness of religious research improve students’ abilities and skills? The study employs a mixed-methods approach, with quantitative data obtained through pre-tests and post-tests administered to students, while qualitative data is gathered through interviews, classroom observations, and student assignment analysis. The results reveal that after implementing religious research, there was a significant improvement in students’ critical thinking skills, understanding of PAI materials, active participation in discussions, and the quality of research assignments. Students also demonstrated an enhanced understanding of PAI materials in a broader and more practical context. Based on pre-test and post-test results, the interval results indicated an increase of approximately 30% - 40% based on measured indicators. The religious research approach was able to create a more dynamic and relevant PAI learning model in line with current needs, proving effective in shaping students who are not only academically excellent but also possess strong contextual abilities. This suggests that religious research can serve as a sustainable learning model to improve the quality of PAI education at the university level.